Model Rekrutmen Calon Anggota Legislatif oleh Partai Politik di DPD Partai Golkar Kabupaten Sidoarjo - Sukmana, Hendra; Arsiyah, Arsiyah (Universitas Muhammadiyah Sidoarjo, 2013)
This research is aimed to study the model of recruitment of prospective members of DPD Golkar sidoarjo. The method of this research used qualitative approach. This research used data sources in the form of primary and secondary data, along with data collection techniques, namely observation, interview and documentation. The technique of data analysis used descriptive analysis by qualitative approach that includes: reduction of data, presentation of data, drawing a conclusion. The research result indicated that the recruitment of prospective members of DPD Golkar Sidoarjo has run well and was not undergoing many changes compared with the previous model of recruitment of prospective members of the party. It began with socialization of registration to the candidate of legislative member toward the volunteers. After that, it continued with self registration by young members of a legislature, join training prepared by team nine, then the candidates will be selected through scoring method.